Inter-rater reliability and validity of scoring men's individual trampoline routines at European championships 2014 - Leskošek, B.; Cuk, I.; Peixoto, C. J. D. (Science of Gymnastics Journal, 2018)
Execution scores of men's individual trampoline routines at the European Championships (EC) 2014 in Guimarães, Portugal were analysed. In total, 66 men competed in the qualifying round. The old, classic format of scoring, by which the execution score is the sum of the scores of individual judges (discarding the lowest and highest scores), was compared with the new format, by which only the median scores of each skill are tripled and then summed for the final score. Execution was found to be the most significant component of the total score, surpassing degree of difficulty and time of flight in both routines. Intra-class correlation (ICC) coefficients and Kendall's coefficient of concordance W were computed. The bias of judging was small with only one judge found who scored significantly higher than the other judges did. Inter-rater reliability was found good for single skills (ICC around .9 and Kendall W around .7), while for the sum of all ten skills it was excellent (all ICC coefficients above .99 and Kendal W above .97) for both routines. Although the correlation coefficients between old and new format scores were high (r=.965 and r=.997 for first and second routine, respectively), there were some substantial differences in rankings of competitors between old and new scoring format (Spearman rank correlation rho=.94 and rho=.96 for first and second routines, respectively). Despite the reliability and validity of judging trampoline routines were high, some possible means of improvement are suggested. Regarding the differences between old and new formats, no clear (dis)advantages of one or another were found.